REPRESENTASI KOGNITIF LOTS, MOTS, DAN HOTS DALAM UJIAN MADRASAH AKIDAH AKHLAK: UPAYA PENJAMINAN MUTU AKADEMIK - Syaiful Huda; M. Habiburrahman (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze and map the distribution of cognitive representation across Low Order Thinking Skills (LOTS), Middle Order Thinking Skills (MOTS), and High Order Thinking Skills (HOTS) within the Akidah Akhlak Madrasah Examination (UM) instrument for the 2025/2026 academic year at MA Manba'ul Ulum Kabul. A descriptive quantitative approach utilizing the content analysis method was employed to dissect the master blueprint document and 45 examination items, comprising 40 multiple-choice questions and 5 essays. Data collection was conducted through documentation techniques, while the analysis utilized a codification sheet based on the revised Bloom's Taxonomy matrix. The findings revealed that the cognitive level distribution consisted of LOTS (Level 1) at 24.44% (11 items), MOTS (Level 2) as the dominant content at 53.33% (24 items), and HOTS (Level 3) at 22.22% (10 items). On a macro level, the construction of this evaluation instrument successfully meets the standardized ideal proportions and aligns with the curriculum mandate of KMA Number 183 of 2019. This research uncovers a research gap in the form of a minor discrepancy between the teacher's administrative documents (12 LOTS, 23 MOTS, 10 HOTS) and the researcher's objective verification results. This shift confirms the necessity of regular academic supervision by the madrasah headmaster and serves as a recommended model for school-level assessment quality assurance management.